Poetry in Popular Songs: towards a Systematic Model for its Representation - Badía Fumaz, Rocío (Pasavento. Revista de Estudios Hispánicos, 2022)
This paper aims to explore the relationships between poetry and music to propose a systematic model to deal with the different forms of appearance of poetry in contemporary popular song. Three phenomena will be examined: a) the consideration of the lyrics as a poem (intrinsic intermediality), going through the lyrical features of the lyrics, but also the narrative a dramatic ones, rejecting a total identification between poetry and songs; b) the effective presence of a previous poem in a song (extrinsic intermediality), to different degrees, and both at the level of the lyrics and at the level of music, an aspect that has hardly been studied; and c) the lyrical reception of a non-poetic text due to its transformation into a song, which will lead to question both the variations that are introduced in the lyrics and the values ​​that it acquires when received with the music. In addition, other problems will be pointed out, related above all to reception, such as the conflictive notion of authorship in the transition from literature to song, the importance of performance in the construction of literary meaning or the use of intermediality as an instrument of power.